2001
DOI: 10.1073/pnas.121169698
|View full text |Cite
|
Sign up to set email alerts
|

Germ line deletion of the CD1 locus exacerbates diabetes in the NOD mouse

Abstract: Quantitative and qualitative defects in CD1-restricted natural killer T cells have been reported in several autoimmune-prone strains of mice, including the nonobese diabetic (NOD) mouse. These defects are believed to be associated with the emergence of spontaneous autoimmunity. Here we demonstrate that both CD1d-null NOD and CD1d-null NOD͞BDC2.5 T cell receptor transgenic mice have an accelerated onset and increased incidence of diabetes when compared with CD1d ؉/؊ and CD1d ؉/؉ littermates. The acceleration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 31 publications
9
107
1
3
Order By: Relevance
“…The data presented in this article confirm that NKT cells are implicated in type 1 diabetes. One should mention, however, that in our present study, both mouse strains (CD1d Ϫ/Ϫ and wild type) showed a similar type 1 diabetes incidence, a finding in clear contrast with another report (37), but in the line of that of Van Kaer (38), who provided us with the mice used here. If NKT cells are indeed involved in the OM-85-mediated protection, it will be important to determine which component within OM-85 stimulates NKT cells and what mechanisms mediate NKT cell involvement.…”
Section: Discussioncontrasting
confidence: 56%
“…The data presented in this article confirm that NKT cells are implicated in type 1 diabetes. One should mention, however, that in our present study, both mouse strains (CD1d Ϫ/Ϫ and wild type) showed a similar type 1 diabetes incidence, a finding in clear contrast with another report (37), but in the line of that of Van Kaer (38), who provided us with the mice used here. If NKT cells are indeed involved in the OM-85-mediated protection, it will be important to determine which component within OM-85 stimulates NKT cells and what mechanisms mediate NKT cell involvement.…”
Section: Discussioncontrasting
confidence: 56%
“…Further, increasing the number of endogenous iNKT cells through V␣14J␣18 TCR transgenesis increases IL-4 production by NOD transgenics and protects them from TID (30). Moreover, the absence of NKT cells in NOD.129-CD1d 0/0 mice increased TID incidence (9,31) even in males, which ordinarily have delayed onset and relatively lower disease incidence compared with female NOD mice (9). Together these findings underscore the role of iNKT cells in downregulating autoimmune responses in vivo.…”
mentioning
confidence: 58%
“…The genetic control of NKT cell numbers in NOD mice was mapped to type 1 diabetes loci [71]. CD1d deficient mice developed diabetes earlier, had a greater disease penetrance and more severe disease [72,73]. In concordance, upregulation of CD1d expression restored the immunoregulatory function of NKT cells and prevented autoimmune diabetes [74].…”
Section: Type 1 Diabetesmentioning
confidence: 76%